Peran Pendapatan Sebagai Mediasi Antara Pengaruh Tingkat Perkembangan Ekonomi Digital Terhadap Kinerja Bisnis UMKM di Kota Lhokseumawe - Maulida, Intan; Febriansyah, Sutan; Wahyuni, Sri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to analyze the impact of the level of digital economy development on the business performance of MSMEs in Lhokseumawe, with income as a mediating variable. The study sample consisted of 96 MSMEs selected using the Slovin technique. Data were analyzed using the PLS-SEM second-order model with an embedded two-stage approach. The results show that the digital economy has a positive and significant effect both directly (p-value=0.000, t-statistic=10.201) and indirectly through income (p-value=0.000, t-statistic=5.979) on the business performance of MSMEs. Income also has a positive and significant impact on business performance (p-value=0.000, t-statistic=4.934) and can partially mediate (VAF=41.4%) the relationship between the digital economy and business performance. In conclusion, the digital economy and income play a crucial role in enhancing the business performance of MSMEs. Digitalization is key for MSMEs to strengthen their competitiveness and achieve sustainable growth. Therefore, focusing on digital strategies that enhance income is essential for MSMEs in this digital era.